Perspectives: client–agency opportunism: how does it happen and what can we do about it?. Issue 8 (17th November 2019) - Chohan, Raeesah; Watson, Richard; Pitt, Leyland
Abstract: While it is seldom spoken about openly, opportunism always prevails in client–agency relationships and could lead to their demise. This study directs attention to client–agency opportunism by describing how it happens and ends with a discussion on how today's client–agency dynamics can be improved.